Assessment of Alcohol and Tobacco Use Disorders Among Religious Users of Ayahuasca - Barbosa, Paulo Cesar Ribeiro; Tófoli, Luís F.; Bogenschutz, Michael P.; Hoy, Robert; Berro, Lais F.; Marinho, Eduardo A. V.; Areco, Kelsy N.; Winkelman, Michael J. (Frontiers in Psychiatry, 2018)
The aims of this study were to assess the impact of ceremonial use of ayahuasca--a psychedelic brew containing N,N-dimethyltryptamine (DMT) and β-carboline --and attendance at União do Vegetal (UDV) meetings on substance abuse; here we report the findings related to alcohol and tobacco use disorder. A total of 1,947 members of UDV 18+ years old were evaluated in terms of years of membership and ceremonial attendance during the previous twelve months. Participants were recruited from 10 states from all major regions of Brazil. Alcohol and tobacco use was evaluated through questionnaires first developed by the World Health Organization and the Substance Abuse and Mental Health Services Administration. Analyses compared levels of alcohol and tobacco use disorder between the UDV and a national normative sample (n=7,939). Binomial tests for proportions indicated that lifetime use of alcohol and tobacco was higher in UDV sample compared to the Brazilian norms for age ranges of 25-34 and over 34 years old, but not for the age range of 18-24 years old. However, current use disorders for alcohol and tobacco were significantly lower in the UDV sample than the Brazilian norms. Regression analyses revealed a significant impact of attendance at ayahuasca ceremonies during the previous twelve months and years of UDV membership on the reduction of alcohol and tobacco use disorder.